Analisis Penerapan Sistem Manajemen Keselamatan Sisi Udara di Bandar Udara Tunggul Wulung Cilacap - Rachman Wibowo, Arief; Kifni Yudianto (MES Management Journal, 2025)
The increasing aviation industry, the implementation of a safety management system is expected to be able to overcome the occurrence of aviation traffic accidents and reduce the number of aviation accidents. Aircraft accidents continue to overshadow the rapid development of the aviation industry in Indonesia. There were 19 accidents and 26 major incidents in 2016, according to data from the National Transportation Safety Committee (KNKT). There were eleven aircraft accidents and seventeen major incidents in 2015, therefore, this shows an increase. Reported from KOMPAS TV explains "There was an air traffic accident at Tunggul Wulung Airport, Central Java, where the PK-RTZ training aircraft belonging to GFS (Genesa Flying School) had an accident during aerobatics in the air at Tunggul Wulung Airport, Cilacap which caused the aircraft to crash and hit the aircraft hangar. The incident occurred on Tuesday, March 20, 2018 at 15:20 WIB. The training aircraft was piloted by MJ. Hanafie from Malang, previously the aircraft took off from Tunggul Wulung Airport at around 14.02 WIB, then at 15.15 WIB performed aerobatics while practicing aerobatics for the graduation of Genesha Flight Academy students". At Tunggul Wulung Airport, Cilacap, the aircraft crashed into the apron and hangar of Perkasa Flight School after losing lift and descending too low. Tragically, pilot Hanafie lost his life in the incident, and his body was sent to Pertamina Hospital, Cilacap. This study uses qualitative research. The methods used in data collection in this study are interviews, observations and documentation as support to answer the formulation of research questions. The results of this study are that Tunggul Wulung Airport is quite good at implementing an airside safety management system, it only needs to be improved in several aspects such as audit and supervision activities which are included in the pillars of safety policies and targets where this must be improved so that every aspect, whether in the form of facilities or other places, can function optimally. The factors that inhibit the implementation of the airside safety system at Tunggul Wulung Airport are the lack of airport safety support facilities, the incompetence of the personnel on duty, the suboptimal use of the Air Traffic Reporting Information System, and indications of a lack of regular maintenance in both the Airside and Landside areas.